ALPHA-1 MICROGLOBULIN: A MARKER FOR EARLY DETECTION OF TUBULAR DISORDERS IN DIABETIC NEPHROPATHY - Shore, Najla; Khurshid, Rukhshan; Saleem, Mahjabeen (Journal of Ayub Medical College Abbottabad, 2010)
Background: Tubular damage as suggested by tubular proteinuria is a recognised feature of glomerulonephritis. The objectives of the study were to compare the level of Î±-microglobulin in normal and diabetic patients, and also to find out whether the level of α-1 microglobulin could become a laboratory marker for tubulo-interstitial damage in diabetic nephropathy. Methods: Twenty-nine registered Type II diabetic patients of either sex were studied. The patients' age ranged from 41-50 years who were admitted in the medical ward, and those who visited the outdoor department of Sir Ganga Ram Hospital, Lahore were included in the study. The duration of study was one year from June 2006 to June 2007. Ten normal subjects with no history of diabetes were taken as controls. Blood samples and 24 hour urine samples of patients of all groups were collected. The levels of urinary protein and blood sugar were estimated by auto analyser. Proteinuria positive urinary samples were analysed by SDS-PAGE electrophoresis. Results: The level of α-1 urinary protein was significantly increased in the group of diabetic patients as compared to the urinary protein level of normal subjects. Blood sugar level was also significantly increased in patients as compared to controls. Level of low molecular weight protein α-1 microglobulin showed an electrophoresis band of 28 Kda with an average volume of 6741.88 in the urine sample of patients. On the other hand, a very light, hardly recognisable band was observed in normal subjects. Conclusion: Urinary α-1 microglobulin provides a noninvasive and inexpensive diagnostic alternative for the diagnosis and monitoring of urinary tract disorders, i.e., early detection of tubular disorders of diabetic nephropathy. We propose that SDSPAGE electrophoresis is a comparatively inexpensive diagnostic approach to detect this marker in the urine sample. Keywords: Alpha-1 microglobulin, diabetic nephropathy, marker, urinary